2017
DOI: 10.3350/cmh.2016.0088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of patients with hepatocellular carcinoma complicated with bile duct invasion

Abstract: Background/AimsLittle is known about the treatment or outcomes of hepatocellular carcinoma (HCC) complicated with bile duct invasion.MethodsA total of 247 consecutive HCC patients with bile duct invasion at initial diagnosis were retrospectively included.ResultsThe majority of patients had Barcelona Clinic Liver Cancer (BCLC) stage C HCC (66.8%). Portal vein tumor thrombosis was present in 166 (67.2%) patients. Median survival was 4.1 months. Various modalities of treatment were initially employed including su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…In previous studies about the icteric type of HCC, patients with bile duct invasion were most likely to have a poor prog- nosis because of the strong association with vascular invasion and PVTT. 7 In those studies, PVTT was present in up to 88% of cases with bile duct invasion. In our results, PVTT was found in 62% of patients with hyperbilirubinemia and 54% of patients without hyperbilirubinemia; however, PVTT was not a significant factor affecting overall survival in the univariate analysis (Table 3).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In previous studies about the icteric type of HCC, patients with bile duct invasion were most likely to have a poor prog- nosis because of the strong association with vascular invasion and PVTT. 7 In those studies, PVTT was present in up to 88% of cases with bile duct invasion. In our results, PVTT was found in 62% of patients with hyperbilirubinemia and 54% of patients without hyperbilirubinemia; however, PVTT was not a significant factor affecting overall survival in the univariate analysis (Table 3).…”
Section: Discussionmentioning
confidence: 86%
“…According to the results of previous studies reported to date, HCC patients with bile duct invasion showed a worse prognosis than patients without bile duct invasion. 7,20 Thus far, TACL is the only treatment modality for controlling intrahepatic tumor lesions in patients with bile duct invasion; however, the efficacy and safety of the treatment are still controversial. 11 Radiofrequency ablation can cause life-threatening complications such as structural injuries in bile ducts or intrahepatic vessels, and transarterial radioembolization or radiation therapy as an alternative to TACL are not commonly used methods for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As conservative treatment, transarterial chemoembolization or radiofrequency treatment was considered. However, liver function is not always favorable for these conservative treatments, therefore, endoscopic biliary drainage should be considered as the first step in non-surgical treatment for such cases [8].…”
Section: Discussionmentioning
confidence: 99%
“…Representing the prevalent primary hepatic malignancy, hepatocellular carcinoma (HCC) is concurrently the sixth most common cancer worldwide and the third dominant cause of mortality due to cancer (1,2).…”
Section: Introductionmentioning
confidence: 99%